Role of Instructional Leadership in Improving Teaching Learning Process in Public Secondary Schools of Sargodha - Jabeen, Farhat; Malik, Muhammad Shafi; Fatima, Sardar (Annals of Human and Social Sciences, 2023)
This study aimed to explore the role of instructional leadership in improving teaching learning process in public secondary schools of Sargodha. Mixed method research was used for this study. Sample consisted of 200 teachers and 15 head teachers. Questionnaire was for teachers and head teachers were interviewed. The Results indicates that mean scores for all factors of instructional leadership which were all higher than mid-point describes that head teachers were practicing instructional leadership to a great extent as perceived by the teachers and there were no significant gender differences in the perception of teachers about instructional leadership. The findings indicates that head teachers view instructional leadership as crucial for improving the teaching and learning process, as it helps create a conducive environment that has a significant impact on teaching learning Process. It is highly recommended that head teachers should encourage collaboration among teachers through regular team meetings, professional learning communities.